Analysis of Drosophila melanogaster reproduction and preadult mortality after the influence of microwave radiation - Gorenskaya, O.; Rybak, D.; Rybak, N.; Horenskyi, H.; Shckorbatov, Yu. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2020)
A new type of anthropogenic impact – low-intensity electromagnetic radiation of extremely high frequencies (EHF EMR) demonstrates various genetic effects. The questions of the organism adaptive response formation to short-term exposure of EMR that depends on the individual’s genotype are of particular interest. The objective of this study was to analyze the reproductive ability and preadult mortality in Drosophila melanogaster with whiteapticot mutation after the influence of microwave radiation. We used D. melanogaster stocks that carry whiteapticot mutation, but differ in the genetic background on which this mutation is located: wa(C-S), wa(Or) and wa. Virgin flies were irradiated. The parameters of the external influence were power flux density W=10 μW/cm2, frequency F=65 GHz, exposure time t=5 minutes. The stages of embryo death, number of adult offspring, and mortality rate at the pupal stage were analyzed. The results of the study showed that the effect of electromagnetic radiation on virgin imagoes of Drosophila with an impaired tryptophan metabolism modifies the survival rate of the offspring at the preimaginal stages of ontogenesis. In the offspring of young flies (at the age of 3–8 days) the frequency of embryonic mortality decreases during the 0–5.5 hours period (initial stages of cleavage and blastoderm formation) and 5.5–17 hours period (stage of gastrulation and embryo segmentation, histogenesis) of embryogenesis. The total number of offspring at the adult stage does not differ from the control values; the mortality rate at the pupal stage also does not change in the offspring of young parents after exposure to EMR. An increase in the age of parental couples that were exposed to short-term EMR on the first day after eclosion from pupae (20–25 days aged) leads to a decrease in the embryonic mortality rate of offspring during the 17–22 hours of embryogenesis (organogenesis stage and larval exit from chorion). The total embryonic mortality rate is determined solely by the age of the parents. The strength of this factor for the stocks is h2wa=69.7 %, h2wa(C-S)=52.2 % and h2wa(Or)=64.9 % respectively. The impact of EMR affects the embryonic mortality rate only for the wa(Or) (h2EMR=18.3 %). External exposure does not change the number of imago offspring in individuals aged 0–5 days; the number of adult offspring increased by 1,2 times in individuals aged 20–25 days in the stock wa(C-S). A decrease in the number of dead individuals at the pupal stage in the descendants of 20–25-day-old parents after exposure to EMR EHF on average by three times was shown.